Quality assurance in tertiary education: A discussion of current developments and practices - Bill Grote (Flexible Learning Association of New Zealand, 2012)
The focus of quality assurance (QA) in the tertiary education sector has shifted from an emphasis on peer review and other internal quality measures to a greater use of external auditing agents. These changes are being driven by governments who demand greater transparency and accountability as they simultaneously withdraw from fully funding the sector. A study of QA processes in Australia, the UK, NZ and the US at the national level and of Open and Distance Learning at institutional level, revealed a sector under stress, subject to rapid change and ongoing government scrutiny. The approaches to QA in these four countries are evolving along similar lines. If there is sufficient convergence, then the foundations are created for an international quality system that would reflect the new global education market place